Komparasi Sistem Pendidikan di Amerika Serikat dan Indonesia - Budiman Akli; Komarudin Sassi; Dwi Noviani (CV. Alim's Publishing, 2024)
This research discusses the education system in the United States and at the end of the discussion a little comparison with the education system in Indonesia. Because of its focus, the discussion of this paper is more directed at the implementation of education systems and policies in the United States including; how the level of education in the United States, management, curriculum, learning evaluation, teacher quality, education funding and education quality assurance practices, which are applied in developing education. The approach used through the method used by the author in conducting this research is through descriptive qualitative methods by searching for various data from documents and literature in the form of; literature, articles, books, other supporting websites including podcasts and video interviews on YouTube that have been directly involved in education in the United States. It is assumed that since the United States declared independence from Great Britain on 4 July 1776, the form of government of the Federal Presidential Constitutional Republic and Liberal Democracy with three branches of government, namely, executive, legislative and judicial, has progressed in various aspects including in the aspect of education. In this context, of course, progress in various fields in Indonesia is far behind compared to the United States, especially in the field of education. From this analysis, it is not wrong if Indonesia continues to improve and take valuable lessons from the United States experience in the education system in this contemporary era.